Lumbar metastases in nasopharyngeal carcinoma (NPC) patient with uncomplete chemoradiation - Andil Mulya; Lily Setiani (Trends in Infection and Global Health, 2023)
Nasopharyngeal carcinoma (NPC) is a tumor arising from the epithelial cells that cover the surface and line the nasopharynx. In Indonesia, NPC is the 4th most prevalent. Nasopharyngeal Carcinoma stage IVB as distant metastasis. The therapy in nasopharyngeal carcinoma (NPC) is Chemoradiotherapy. Concurrent chemoradiotherapy is either an established treatment modality or actively being investigated. Chemoradiotherapy have demonstrated decreased incidence of distant metastases compared with radiation only, however only if its treatment done completely. Here we present a rare case of unfinished chemoradiotherapy that caused metastases nasopharyngeal carcinoma patient. A 41-years-old consulted to ENT-HN department with main complaints of progressive cancer pain for 3 month and got worse in past 1 month. Patient also complaints for the pain at the waist, chest and headache currently. However, there was formal history of nasopharyngeal carcinoma for this patient since 2019 that had been treated with 3 cycles of chemotherapy and 26 cycles of radiotherapy. The patient was diagnosed with recurrent nasopharyngeal carcinoma post chemotherapy and radiotherapy with metastatic process. Unfortunately, the treatment underwent was not complete. A nasopharyngeal biopsy was performed and the histopathology result revealed a non-keratinizing squamous cell carcinoma nasopharynx. Lumbar CT-scan showed distant metastatic to lumbar vertebrae I-V. Nasopharyngeal carcinoma (NPC) represents a rare disease that showed as carcinoma that appears in the nasopharynx. The unfinished treatment of NPC leads to recurrent NPC and metastatic process to lumbar vertebrae I-V. Nevertheless, 20% of patients are radioresistant and experience a recurrence, which in most cases manifests with distant metastases.